Antidiabetic effects of fennel leaf aqueous extract in alloxan-induced diabetic rats - Mahdi Noureddini; Maryam Akbari; Zeinab Vahidinia; Samaneh Sadat Alavi; Majid Nejati; Mohammad Ali Atlasi (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Diabetes Mellitus is a common chronic metabolic disease in the world population. There is evidences on the anti-hyperglycemic effects of different parts of fennel; however, the reports about antidiabetic activity of fennel leaves are not enough. In this experiment, effects of fennel leaf aqueous extract on biochemical alterations and the histopathology of the pancreas in alloxan induced diabetic rats were studied. Methods Fifty adult male rats were divided into five groups: the non-diabetic and the diabetic control groups, and three diabetic groups treated with different doses of fennel leaf extract (50, 100 and 200 mg/kg/day). Blood glucose, body weight, serum insulin and C-peptide levels were determined. The pancreas histology was evaluated by preparation of paraffin sections. They were stained using hematoxylin and eosin stain. Morphometrically, the mean number and the area of the islets of Langerhans were measured. Results Fennel leaf extract in different doses caused a reduction in blood glucose, and an increase in body weight, serum insulin and C-peptide. In diabetic treated rats, fennel leaf extract significantly increased the number and area of the Islets of Langerhans. Conclusions Our results indicated the anti-hyperglycemic effects of fennel leaf extract and morphologic improvement of the pancreatic islets of Langerhans in alloxan induced diabetic rats.